Causality Effect Among ASEAN-5 Stock Markets in COVID-19 Pandemic: VAR Model Approach - Fatah, Bintang Izzatul; Jody, Jody; Budiasih, Budiasih (Enthusiastic : International Journal of Applied Statistics and Data Science, 2023)
Financial globalization increase integration degree of capital flow. However, the global shock could impact many countries, either positive and negative. COVID-19 pandemic is one of the shock that affect world including ASEAN-5. This paper apply the Vector Autoregressive (VAR) model to identify the linkage among ASEAN-5 stock markets during the COVID-19 pandemic and it is used because of no spesific theory behind it. The data used in this paper is the weekly return of the composite index of ASEAN-5 stock markets from 11 March 2020 to 29 December 2021. This paper finds that there is a linkage among ASEAN-5 stock markets indicated by decreasing price index consecutive. Therefore, the implication of this paper is that the investors have to switch the investment instrument from stock to other instrument carefully. Once the negative impact begins to taper off, investors could do international stock investment.